Pengaruh Metode Tutor Sebaya terhadap Prestasi Belajar Matematika Siswa Kelas IV di SD Negeri 1 Surabaya - Misbah, Fitria Mayasari (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aims to determine the effect of peer tutoring methods on mathematics learning achievement with mixed operation material among fourth-grade students at SD Negeri 1 Surabaya. This research employs a quasi-experimental design. The population of the study consists of all fourth-grade students at SD Negeri 1 Surabaya. The sample was determined by directly observing a single group of subjects under two conditions without a comparison group, making each subject their own control group. The research design used is a one group pre-test post-test design. Data collection techniques involve achievement tests. The data were analyzed using simple linear regression analysis. The results indicate that the learning achievement data were analyzed using a t-test, resulting in rhitung = 0.859 and rtabel = 0.374 at a 5% significance level, meaning H0 is rejected and Ha is accepted. For the significance test, thitung > ttabel was obtained, specifically 7.88 > 0.374, thus it can be concluded that there is an effect of the peer tutoring method on mathematics learning achievement with mixed operation material among fourth-grade students at SD Negeri 1 Surabaya for the 2016/2017 academic year.